Efektivitas Kinerja Inkubator Bisnis Selama Pandemi Covid-19 Dari Perspektif Tenan: Studi Kasus Di KKIB Universitas Diponegoro - Omia Crefioza; Amie Kusumawardhani (Universitas Batanghari Jambi, 2021)
This study aims to analyze the effectiveness of the performance of the Undip KKIB business incubator while Covid-19 pandemic from the tenant's point of view. The method used in this research is the qualitative method. This study uses primary data in the form of interviews within two tenants as informant The results of this study indicate that there has been a decrease in quantity in several programs during the Covid-19 pandemic, such as mentoring, coaching, business matching, and pitching activities. However, in terms of quality, the training provided by the Undip KKIB business incubator has been good in terms of services and incubator programs that exceed tenants' expectations. The effectiveness of the incubator is also viewed in terms of the tenant's business growth has been getting better since joining the business incubator even though it is currently in a polemic of the Covid-19 pandemic. For future researchers, examine more deeply the effectiveness of the performance of university business incubators during the Covid-19 pandemic from different aspects is expected.